Keeping up with changing times: Student leaders, resilience, fragility and professional development (Journal of Student Affairs in Africa, 2022)
The Fallist movements of 2015/16 brought about rapid changes in the South African higher education space, which required student leaders to rethink their role as agents of change and transformation. Student leaders contribute as stakeholders and decision-makers in student governance, and some find themselves in a context where their working and living spaces become increasingly entangled. This is a particularly challenging context, where they are encouraged to think beyond the professional-personal binary. In this paper, we focus on the challenges student leaders face as peer educators in both on- and off-campus residences. The resilience and fragility of student leaders, and how these play out in their experiences at the University of the Free State, will be highlighted. The importance of self‑reflection, resilience and fragility in professional development will be explored. Through a study that included survey data as well as arts-based methods, we engaged with student leader experiences in order to understand how they negotiated challenges in a space of transformation and constant change. We found arts-based research to complement and support the more conventional data-gathering process. Our paper thus highlights how methodological inventiveness can address new and different questions that arise in our rapidly changing space. Through this, we hope to zoom in on the complex micro-social experiences of student leaders who live in spaces of transformation. Student leaders are in a unique position as people who live and work in the student community, and their role as peer educators remains unexplored. In this paper, we hope to contribute to a body of knowledge that could foreground student leadership in relation to transformed pedagogy.
Keywords: student leadership; resilience; methodological inventiveness; transformation; leadership training